2021
DOI: 10.1007/s00339-021-05166-5
|View full text |Cite
|
Sign up to set email alerts
|

Study on optimizing c-axis oriented AlN thin film for piezoelectric sensing applications controlling the sputtering process parameters

Abstract: The crystal orientation of aluminium nitride (AlN) thin film poses a challenge in piezoelectric applications, where the orientation of ( 002) is desired for obtaining a high piezoelectric coefficient of the order of 10 -12 V/m. Many processes to develop c-axis oriented AlN films with optimized parameters are reported specifically for piezoelectric applications. Of these, the sputtering has been a promising process with control over the target to substrate alignment angle and distance, sputtering parameters, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Nevertheless, with a rise in the N 2 ow rate up to 40%, there is a gradual rise in the AlN content within the lm, resulting in a signi cant improvement in transmittance and achieving a higher level of overall transmittance. Several studies [24][25][26] have reported that using the DC magnetron sputtering technique can produce AlN thin lms with transmittance above 80% in the range of visible light wavelengths. Thin lms of AlN exhibit exceptional optical and electronic properties, characterized by a high refractive index and excellent transmittance, rendering them highly suitable for a wide range of applications.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, with a rise in the N 2 ow rate up to 40%, there is a gradual rise in the AlN content within the lm, resulting in a signi cant improvement in transmittance and achieving a higher level of overall transmittance. Several studies [24][25][26] have reported that using the DC magnetron sputtering technique can produce AlN thin lms with transmittance above 80% in the range of visible light wavelengths. Thin lms of AlN exhibit exceptional optical and electronic properties, characterized by a high refractive index and excellent transmittance, rendering them highly suitable for a wide range of applications.…”
Section: Resultsmentioning
confidence: 99%